(untitled) (Global Journal of Management and Business Research, 2022)
Purpose: This study explores the impact of work from home on the work-life balance of professionals mainly in two sectors and also finds out the preference for work modality Design/methodology/approach: We adopted a qualitative research design using a multiple case study method collecting data from six respondents working in different companies in Bangladesh.